2019
DOI: 10.3390/ma12132105
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steel Fiber Tensile Strengths and Aspect Ratios on the Fracture Properties of High-Strength Concrete

Abstract: Steel fiber embedded in concrete serves to reduce crack development and prevent crack growth at the macroscopic level of the concrete matrix. Steel fiber-reinforced concrete (SFRC) with high compressive concrete strength is affected primarily by the dimensions, shape, content, aspect ratio, and tensile strength of the embedded steel fiber. In this study, double-ended hook steel fiber was used in SFRC with a concrete compressive strength of 80 MPa. This fiber was used for the study variables with two aspect rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 8 publications
(11 reference statements)
1
35
0
Order By: Relevance
“…The performance of concrete under tension can be substantially improved by the addition of steel fibers since SFRC exhibits increased tensile strength and mainly post-peak deformation capability showing pseudo-ductile behavior due to the gradual debonding failure of the fibers [ 78 ]. Various analytical stress versus strain expressions have been proposed to simulate the SFRC tensile behavior [ 79 , 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…The performance of concrete under tension can be substantially improved by the addition of steel fibers since SFRC exhibits increased tensile strength and mainly post-peak deformation capability showing pseudo-ductile behavior due to the gradual debonding failure of the fibers [ 78 ]. Various analytical stress versus strain expressions have been proposed to simulate the SFRC tensile behavior [ 79 , 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…The macro fibers produced the best performance in most of the investigated parameters, under both tension and compression. This phenomenon could be explained through the highest aspect ratio of the macro fibers, equaling to 100, since the higher aspect ratio would produce the higher mechanical property of the composites [5,10,11]. In contrast, the micro fiber, having its lowest aspect ratio of 65, would produce the lowest mechanical property.…”
Section: Materials and Preparation Of Specimensmentioning
confidence: 99%
“…After demolding, the specimens were water-cured at 25 °C for 14 days. Next, the specimens were removed from the water tank and dried at 70 °C in a drying oven for at least 12 h. All the specimens were tested at the age of 18 On the other hand, the mechanical properties of SFCs have been reported to be dependent much on fiber characteristics, e.g., fiber aspect ratio (length/diameter ratio), fiber size and shape, fiber volume content, fiber material [4][5][6][7][8][9]. Also, in the process of making SFCs, the fiber type and fiber content greatly affected the probability of heterogeneous fiber distribution and fiber flocculation governing workability and viscosity of a concrete mixture [6].…”
Section: Introductionmentioning
confidence: 99%
“…He found that by adding coconut fiber, compressive and flexural strengths were increased to 13% and 9%, respectively. However, in terms of durability, the chloride diffusion resistance was reduced [10] Previous studies have confirmed that fiber can improve the mechanical properties of concrete [11][12][13][14][15][16], but there are different opinions on the chloride diffusion resistance. Some researchers think that fiber can enhance the chloride diffusion resistance of concrete, but the other researchers hold the opposite opinion.…”
Section: Introductionmentioning
confidence: 99%